Network for Cooperation in Integrated Water Resource Management for Sustainable Development in Latin America and the Caribbean No. 29 - NU. CEPAL (ECLAC, 2015)
Editorial remarks.-- Open discussion: Drinking water supply and sewerage services in the city of Buenos Aires, Argentina ; Regulatory accounting ; A new regulatory model in Bolivia.-- News of the Network: World Water Day 2009 ; Water Protection Fund (FONAG) ; Matanza Riachuelo River Basin Authority ; Internationalization and business strategies in the electricity industry.-- Meetings: Regional Conference on Policies for Drinking Water and Sanitation Services.-- Internet and WWW News